Über die Konvergenz der Fakultätenreihen - Gandler, M. E.; Golossowa, E.; Naftalewitsch, A. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: М. Гандлер, Э. Голосова и А. Нафталевич. О сходимости факториальных рядов M. Gandler, E. Golosova ir A. Naftalevičius. Faktorialinių eilučių konvergencija